MAKNA PENDIDIKAN BAGI KAUM MARJINAL (Studi Terhadap Pandangan Tukang Becak di Pasar Sangkapura Bawean) - Mahfud; Sofiyatun (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2015)
Education is the main institution that plays a critical role in establishing and cultivate civilization. Reciprocation of a nation is strongly influenced by the existence of education. So it is necessary to note how the views of the marginalized (pedicab driver) about the value of education and how their ideals to the future of their children through educational institutions are. To find them out, this research uses field research by qualitative method using inductive data analysis. From the field data is then acquired answers about the meaning of education, and their ideals about the education of their children. And for that, the marginalized (pedicab driver) think that education has a very important meaning, their ideals are same, that they want their children to be better human beings through education.